Chlorido(dimethyl sulfoxide)(pyridine-2-thiolato N-oxide-κ(2) S,O)platinum(II) - Ravindran Durai Nayagam, B. (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, [Pt(C(5)H(4)NOS)Cl(C(2)H(6)OS)], contains two independent complex molecules having similar geometries. Each Pt(II) atom is four-coordinated in a distorted square-planar geometry by S and O atoms of one pyridine N-oxide ligand, the S atom of one dimethyl sulfoxide molecule and one terminal Cl(−) ion. The molecules are linked into a three-dimensional framework by C—H⋯O and C—H⋯Cl hydrogen bonds.